Age‐related reproductive performance of the Adélie penguin, a long‐lived seabird exhibiting similar outcomes regardless of individual life‐history strategy. Issue 4 (1st February 2021) - Kappes, Peter J.; Dugger, Katie M.; Lescroël, Amélie; Ainley, David G.; Ballard, Grant; Barton, Kerry J.; Lyver, Phil O'B.; Wilson, Peter R.
Abstract: Age‐related variation in reproductive performance in long‐lived iteroparous vertebrate species is common, with performance being influenced by within‐individual processes, such as improvement and senescence, in combination with among‐individual processes, such as selective appearance and disappearance. Few studies of age‐related reproductive performance have compared the role of these drivers within a metapopulation, subject to varying degrees of resource competition. We accounted for within‐ and among‐individual changes among known‐aged Adélie penguins Pygoscelis adeliae during 17 years (1997–2013), at three clustered colonies of disparate size, to understand patterns in age‐related reproductive success during early and late adulthood. Age at first reproduction (AFR) was lowest, and number of breeding attempts highest, at the largest colony. Regardless of AFR, success improved with early post‐recruitment experience. For both oldest and youngest recruitment groups, peak performance occurred at the end of their reproductive life span indicating a possible cost of reproduction. Intermediate recruitment groups reached peak performance in their mid‐reproductive life span and with intermediate breeding experience, before decreasing. Breeding success was lowest for the initial breeding attempt regardless of AFR, but we observed subsequent variation relative to recruitment age. Gaining experience by delaying recruitment positively influenced reproductive performance early in the reproductive life span and was most evident for the youngest breeders. Oldest recruits had the highest initial and peak breeding success. Differences in AFR resulted in trade‐offs in reproductive life span or timing of senescence but not in the overall number of breeding attempts. Patterns differed as a function of colony size, and thus competition for resources. Early life improvement in performance at the larger colonies was primarily due to within‐individual factors and at the largest colony, AFR. Regardless of colony size late‐life performance was positively related to the age at last reproduction, indicating selective disappearance of lower performing individuals. These results highlight that different life‐history strategies were equally successful, indicating that individuals can overcome potential trade‐offs associated with early‐ and late‐life performance. These results have important implications for understanding the evolution of life‐history strategies responsible for driving population change. Abstract : Few studies have accounted for both within‐ and among‐individual processes of age‐related reproductive performance of a long‐lived iteroparous species within a metapopulation, subject to varying degrees of resource competition. The authors documented that a metapopulation of Adélie penguins breeding at three different sized colonies were able to overcome trade‐offs associated with early‐ and late‐life performance by adopting alternate life‐history tactics, resulting in equal reproductive performance.